Correlation of ERCC5 polymorphisms and linkage disequilibrium associated with overall survival and clinical outcome to chemotherapy in breast cancer - Khan, Iqra; Masood, Nosheen; Yasmin, Azra (Frontiers in Oncology, 2023)
Aim: ERCC5 is a DNA endonuclease and a nucleotide excision repair gene, its mutations lead to lack of activity by this enzyme causing oxidative DNA damage to progress. This study was aimed to assess the role of four selected single nucleotide polymorphisms (SNPs) of ERCC5 and their linkage disequilibrium associated with survival analysis and clinical outcomes in breast cancer. Methods: Four SNPs (rs751402, rs17655, rs2094258 and rs873601) of ERCC5 gene were analysed by PCR-RFLP technique followed by sequencing in 430 breast cancer (BC) cases and 430 cancer free individuals. Statistical analysis was carried out by MedCalc 17 and SPSS version 24 softwares while bioinformatics analysis of linkage disequilibrium was performed by Haploview software 4.2. Results: Multivariate analysis showed that rs751402 and rs2094258 polymorphisms were significantly associated with an elevated risk of BC (P< 0.001) while the other two SNPs rs17655 and rs873601 variants did not show any association (P> 0.001). Survival analysis revealed that rs751402 and rs2094258 had longer overall survival period (P<0.001) compared with rs17655 and rs873601. Moreover, rs751402 & rs2094258 also had significantly longer overall survival (Log-rank test, P< 0.005) for all the three survival functions (positive family history, ER+PR status, used contraceptives) while rs17655 and rs873601 did not show any significant association. Only rs873601 showed strong negative correlation with all chemotherapeutic groups. Conclusion: The current results inferred that variation in ERCC5 may contribute towards BC development and their genetic anomalies may have a relationship with cancer risk and may be used as a biomarker of clinical outcome.